2003
DOI: 10.1038/sj.ejcn.1601611
|View full text |Cite
|
Sign up to set email alerts
|

Mothers of undernourished Jamaican children have poorer psychosocial functioning and this is associated with stimulation provided in the home

Abstract: Objectives: To compare mothers of undernourished children with mothers of adequately nourished children on maternal depression, parenting self-esteem, social support and exposure to stressors and to determine if these variables are independently related to undernutrition and stimulation provided in the home after controlling for socio-economic status. Design: A case control study. Setting: Children and their mothers were recruited from 18 government health centres in the Kingston, St Andrew and St Catherine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 30 publications
2
43
1
1
Order By: Relevance
“…Increasing evidence of the deleterious consequences of perinatal depression for women's life-long mental health as well as the physical, cognitive, emotional, and psychological development and wellbeing of their children suggests that this is a serious omission. 12,13 A policy focus on reducing health inequalities, 14 improving access to psychological therapy in primary care, 15 delivering race equality in mental health care, 16 and improving the psychosocial wellbeing of mothers and their children 17 suggests that research into the perinatal mental health of women in underserved communities is both necessary and timely.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence of the deleterious consequences of perinatal depression for women's life-long mental health as well as the physical, cognitive, emotional, and psychological development and wellbeing of their children suggests that this is a serious omission. 12,13 A policy focus on reducing health inequalities, 14 improving access to psychological therapy in primary care, 15 delivering race equality in mental health care, 16 and improving the psychosocial wellbeing of mothers and their children 17 suggests that research into the perinatal mental health of women in underserved communities is both necessary and timely.…”
Section: Resultsmentioning
confidence: 99%
“…23,24,[29][30][31][32][33][34][36][37][38][39] Meta-analysis of these studies showed that the relationship between maternal depression and underweight (OR: 1.5; 95% CI: 1.2-1.8) remained similar to that in the meta-analysis of all studies and the heterogeneity persisted (Q = 37.83, P = 0.001). When the meta-analysis was restricted to the nine studies that used measures of depression or depressive symptoms, 24,25,29,31,[33][34][35]38,39 the relationship between maternal depression and underweight strengthened and remained statistically significant (OR: 1.7; 95% CI: 1.2-2.4), and the findings remained heterogeneous (Q = 18.70; P = 0.017). Finally, when the meta-analysis was restricted to the four longitudinal cohort studies, 31,33,35,38 the relationship strengthened further (OR: 2.2; 95% CI: 1.5-3.2) and high homogeneity was noted (Q: 2.47; P = 0.48).…”
Section: Systematic Reviews Pamela J Surkan Et Almentioning
confidence: 99%
“…1), [23][24][25][29][30][31][32][33][34][35][36][37][38][39] covering a combined study population of 13 923 mother and child pairs. The pooled data showed a moderate, statistically significant relationship between maternal depression and underweight (OR: 1.5; 95% confidence interval, CI: 1.2-1.8).…”
Section: Underweight Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The most similar study to the present one was conducted in Jamaica 22 . The authors also compared cases (children with mild to moderate malnutrition) and controls to investigate the role of various maternal and family characteristics -self-esteem, depression, social support, quality of the psychosocial environment (measured by the HOME inventory 15 ) and exposure to stress factors -in the determination of the child's nutritional status, conducting uni-and multivariate logistic regression and including socioeconomic factors in the analyses.…”
Section: Discussionmentioning
confidence: 76%